2021
DOI: 10.1149/10409.0017ecst
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Optimization in the Drying Process of Catalyst Ink for PEFC Electrode Films with Few Cracks

Abstract: Fabrication of the catalytic layers in polymer electrolyte fuel cells (PEFCs) typically involves a powder-film drying process, in which material ink is prepared, coated, and then dried. The process exhibits complex phenomena and requires adjustments of a huge number of parameters to control each phenomenon. We applied Bayesian optimization to determine the temperature profile during the drying process, to obtain electrodes with smooth surfaces. The results suggest that pulsed heat treatments were more effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…6 d). The effect of heating on the formation of the skin and the subsequent defect reduction was confirmed in our previous study 48 . In the samples that continued to be heated at high temperatures even after the skin was formed, radial cracks were observed.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…6 d). The effect of heating on the formation of the skin and the subsequent defect reduction was confirmed in our previous study 48 . In the samples that continued to be heated at high temperatures even after the skin was formed, radial cracks were observed.…”
Section: Resultssupporting
confidence: 78%
“…Moreover, the detailed mechanism of the drying phenomenon could be determined. In our previous study 48 , we confirmed that the parameters determined by BO were partially applicable for this process. However, the effectiveness of the parameter exploration system was not evaluated.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…. , 0] [12,13]. Using the mode shape decomposition method of the structural equation of motion, the vertical displacement y(x, t) of a simply supported beam at a time x and position t can be expressed as a linear combination of beam mode shapes, that is shown in the following formula:…”
Section: Frequency Domain Response Of Beam-tmdi System Undermentioning
confidence: 99%
“…where ϕ j (x) is the first mode shape of the beam, and for a simply supported beam of equal section, the mode shape function is ϕ j (x) � sin(jπx/L); u j (t) is the generalized coordinate corresponding to the j-th mode of the simply supported beam [13]. e virtual acceleration excitation is constructed using the known self-spectrum as follows:…”
Section: Frequency Domain Response Of Beam-tmdi System Undermentioning
confidence: 99%